Inclusion of a tannin-rich legume in the diet of beef steers reduces greenhouse gas emissions from their excreta - Flavia O. S. van Cleef; José C. B. Dubeux; Francine M. Ciriaco; Darren D. Henry; Martin Ruiz-Moreno; David M. Jaramillo; Liza Garcia; Erick R. S. Santos; Nicolas DiLorenzo; João M. B. Vendramini; Harley D. Naumann; Lynn E. Sollenberger (Scientific Reports, 2022)
Abstract The objectives of this study were to determine the emission of nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2), as well as the isotopic composition of N2O from excreta of beef steers fed ‘AU Grazer’ sericea lespedeza hay [SL; Lespedeza cuneata (Dum. Cours.) G. Don]. Fifteen Brahman × Angus crossbred steers were fed one of three experimental diets: 0, 50, or 100% inclusion of SL into ‘Tifton 85’ bermudagrass hay (Cynodon spp.). Gas sampling occurred on days 0, 1, 3, 5, 7, 14, 18, 25, and 32 after urine or feces application to static chambers for two experimental periods. Effect of the day after feces application (P < 0.001), while day × inclusion of SL interaction was observed in urine (P < 0.001) for all greenhouse gases (GHG) analyzed. Peaks of emission of all GHG in urine and feces occurred in the first days (P < 0.001), with days 3 and 5 being most depleted in 15N-N2O in feces, and days 3, 5, and 7, in urine (P < 0.001). Feeding SL to beef steers was effective in mitigating the emission of GHG from the excreta, but further research is necessary to investigate the mechanisms behind the reductions.